Zones of Multifunctional Public Underground Space in the New Master Plan of Moscow. (2016) - Glozman, Olga
Abstract: The article features scientific research work conducted by the author aimed at creating methodology of functional zoning of the underground spaces of the cities. Implementing of this methodology into the process of drafting town planning documentation on Moscow allowed defining the zones of underground spaces on the territory of Moscow which should be reserved in advance in order to be used later for municipal functions. In the course of the academic research work 41 zones were defined by analyzing the entire territory of the city. The methodology of identifying underground territories of the city which can be reserved in the town planning documentation for municipal functions implies consequential comparison of preconditions and restrictions of various levels. All preconditions and restrictions (factors) are differentiated depending on the scale of researched territory and demanded division into three groups. The methodology was fully applied on the territory of Moscow, the analysis becomes more detailed on each stage of the process and new factors were added. Each factor if graphically represented on the map of a city at an appropriate scale: 1:10000, 1:5000, 1:2000. The catalogue featuring the addresses of the zones where it is planned to place multifunctional municipal underground objects was prepared on the grounds of the conducted analysis. 11 zones were defined as suitable for top priority reclamation. Architectural and planning concepts were worked out for these zoned, technical and economic indexes were defined and the engineering workload was calculated. As a result of the conducted research work long range territories for utilizing the underground space were defined and detailed conceptions were prepared for the investors. The results of the research work will be applied to the methodology of developing urban planning documentation. The new master plan for Moscow is being worked out at the moment. For the first time in history the master plan features zones of multifunctional municipal underground spaces.